Fundamentals of technical mathematics - Musa, Sarhan M. (Academic Press is an imprint of Elsevier, 2016)
Fundamentals of Technical Mathematics introduces key, applied mathematics for engineering technologists and technicians. Through a simple, engaging approach, the book reviews basic mathematics, including whole numbers, fractions, mixed numbers, decimals, percentages, ratios, and proportions. The book covers conversions to different units of measure (standard and/or metric) and other topics as required by specific businesses and industries, providing a go-to resource on the topic. Building on these foundations, it then explores concepts in arithmetic, introductory algebra, equations, inequalities, and modeling, graphs and functions, measurement, geometry, and trigonometry, all the while supporting these concepts with practical applications in a variety of technical and career vocations, including automotive, allied health, welding, plumbing, machine tool, carpentry, auto mechanics, HVAC, and many other fields. In addition, the book provides practical examples from a vast number of technologies.